Evolution Law of Longitudinal Deformation Curve and Release Coefficient of Viscoelastic Rock - WANG Jiachen, MENG Lingzan, ZHANG Dingli, LU Song, WEN Ming (Shanghai Jiaotong Daxue xuebao)
Conventional elastic solutions cannot explain the deformation characteristics of soft rock tunnels exhibiting creep behavior. Therefore, a Burgers model is introduced to demonstrate the space-time effects in the construction period of soft rock tunnel. The influences of different factors on the longitudinal deformation behavior of viscoelastic rock as well as the spatiotemporal evolution patterns have been revealed through numerical simulations. An empirical formula for the displacement release coefficient is derived using the response surface method. The feasibility of the proposed method is validated by comparing the results with on-site monitoring data and other theoretical values. The findings indicate that geostress has a negligible effect on the displacement release coefficient. In constrast, the Kelvin shear modulus, viscosity coefficient, Maxwell shear modulus, and excavation speed significantly affect the displacement release coefficient. According to viscosity time, the hysteresis coefficient can be divided into three categories: low, medium, and high. Empirical formulas are fitted for the longitudinal deformation curve, including time, spatial, and spatiotemporal factors. The research conclusion can provide a more convenient method for predicting the deformation of soft rock tunnels.